2019
DOI: 10.3390/diagnostics9040191
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Test for the Determination of Resistant and Susceptible S. aureus and Enterococcus spp. Using a Multi-Channel Surface Plasmon Resonance Device

Abstract: The objective of this study was to investigate the development of a surface plasmon resonance (SPR) sensor platform equipped with multiple channels for the simultaneous determination of methicillin-resistant S. aureus (MRSA), methicillin-susceptible S. aureus (MSSA) and vancomycin-resistant Enterococcus (VRE), and vancomycin-susceptible Enterococcus (VSE). Drug resistance of S. aureus strains against cefoxitin and Enterococcus strains against vancomycin were investigated both using the minimum inhibitory conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…A SEM micrograph analysis showed bacterial cell aggregation without the usual well-defined clustering of S. aureus. This finding is consistent with previous studies that reported the effect of antibiotics on bacterial cells [48,49]. NS alone disrupted the bacterial cell surface and therefore caused destruction, which was evident in the bacterial growth inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…A SEM micrograph analysis showed bacterial cell aggregation without the usual well-defined clustering of S. aureus. This finding is consistent with previous studies that reported the effect of antibiotics on bacterial cells [48,49]. NS alone disrupted the bacterial cell surface and therefore caused destruction, which was evident in the bacterial growth inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Antibiotic susceptibility tests, such as the disk diffusion test, can be used to identify MRSA; the majority of these tests employed cefoxitin because methicillin antibiotic disk is no longer readily available commercially (Anand et al 2009). Antibiotic susceptibility testing has certain disadvantages compared to identifying mecA or PBP2a (Ozkaya et al 2019). S. aureus isolates that are resistant to cefoxitin continued to undergo ORSAB as a phenotypic test; however, depending on conditions like temperature, it may also vary throughout growth (Maharjan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The biosensor correctly identified ten MRSA and ten MSSA clinical isolates compared to the reference method. The system could be adapted to detect multiple pathogens [ 121 ]. Another example of a phenotypic biosensor is the fluorescence resonance energy transfer (FRET) probe-based AST method.…”
Section: Emerging Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%